Agreement between telehealth and face-to-face assessment of intellectual ability in children with specific learning disorder. (August 2019) - Hodge, Marie Antoinette; Sutherland, Rebecca; Jeng, Kelly; Bale, Gillian; Batta, Paige; Cambridge, Aine; Detheridge, Jeanette; Drevensek, Suzi; Edwards, Lynda; Everett, Margaret; Ganesalingam, Kalaichelvi; Geier, Philippa; et al.
Introduction: Access to cognitive assessments for children living remotely is limited. Telehealth represents a potential cost- and time-effective solution. A pilot study was conducted to determine the feasibility of telehealth to assess cognitive function in children with learning difficulties. Methods: Thirty-three children (median age = 9 years 11 months), recruited from the New South Wales (NSW) Centre for Effective Reading, underwent assessment of intellectual ability. Comparisons were made between the intellectual ability index scores obtained by a psychologist sitting face-to-face with the children and another psychologist via telehealth using a web-based platform, Coviu. Results: The telehealth administration method yielded comparable results to the face-to-face method. Correlation analyses showed high associations between the testing methodologies on the intellectual ability indices (correlation coefficient range = 0.981–0.997). Discussion: Findings indicate that telehealth may be an alternative to face-to-face cognitive assessment. Future work in a broader range of cognitive tests and wider range of clinical populations is warranted.